Determination of left ventricular volumes by Simpson's rule in infants and children with congenital heart disease. Issue 2 (February 1989) - Ino, T; Benson, L N; Mikalian, H; Freedom, R M; Rowe, R D
Abstract : Regression equations were developed from left ventricular casts of known volumes to calculate left ventricular volumes from biplane cineangiography obtained in non-standard views. Volumes were calculated by Simpson's rule from casts of postmortem specimens from patients with congenital heart disease. The casts were divided into two groups: those that came from patients with abnormal right ventricular haemodynamic function (group 1, n = 11) and those that came from patients in which it was normal (group 2, n = 9). Biplane cinegrams were taken in conventional (anteroposterior/lateral, right anterior oblique/left anterior oblique) and non-conventional (long axis oblique, hepatoclavicular, and sitting up) projections. The true volume of each cast was determined from its weight and specific gravity. Correlations between measured and true volumes (r = 0.96 to 0.99) were excellent in all projections, although each projection overestimated the true volumes (slope = 0.72 to 0.94). The regression equations obtained from conventional views were significantly different from those from the non-conventional views; however, the regression slopes in group 1 were not different from those in group 2 in any view. Regression equations obtained by Simpson's rule do not seem to be affected by the haemodynamic state of the right ventricle. Different regression equations are required to measure left ventricular volumes from non-conventional angiograms.